The effects of instructional self-talk on quiet-eye duration and golf-putting performance - Sarig, Y.; Ruiz, M. C.; Hatzigeorgiadis, A.; Tenenbaum, G. (The Sport Psychologist, 2023)
While the impact of strategic self-talk on performance is well documented, examination of the attentional-perceptual mechanisms of self-talk is still at early stages. This study`s aim was to examine the effects of instructional self-talk on quiet-eye durations and putting performance. Thirty participants were recruited and randomly assigned to self-talk or control conditions. Participants performed a golf-putting task in a mixed between (self-talk vs. control) and within (pre- vs. postintervention) design. Two 2 × 2 mixed-design analyses of variance were conducted for performance and quiet-eye durations as dependent variables. A mediation analysis was conducted to examine the mediating effect of quiet-eye durations on performance. Results showed that self-talk use led to longer quiet-eye durations and better performance compared with controls. The mediation analysis indicated that performance was mediated by quiet-eye durations. Discussion centers on the role of quiet-eye in motor performance and how self-talk can assist in regulating quiet-eye.